Pemodelan Struktur Bawah Permukaan Berdasarkan Data Mikrotremor di Kecamatan Kampung Melayu, Kota Bengkulu - Hutasoit, Tegar Ashary; Refrizon, Refrizon; Suhendra, Suhendra (Jurnal Fisika Unand, 2025)
Kampung Melayu District in Bengkulu City is experiencing rapid infrastructure development, necessitating early disaster mitigation efforts. This study aims to model subsurface structures using microtremor data to support earthquake disaster mitigation. Microtremor data were analyzed using the Horizontal to Vertical Spectral Ratio (HVSR) method to produce HVSR curves, which were then inverted to determine stratigraphy based on shear wave velocity (Vs30). The results show that the amplification factor (A0) ranges from 1 to 14.49 H/V, indicating varying soil response to seismic waves. The natural frequency (f0) values range from 0.6 to 8.7 Hz, reflecting differences in soil layer thickness and stiffness. The Vs30 values fall within 189–883.9 m/s, representing variations from soft soil to hard rock layers. These parameters were utilized to create spatial distribution maps, illustrating the area’s subsurface characteristics. Based on the seismic parameter distribution, Kampung Melayu District is classified as a medium-risk earthquake zone. This information is expected to support better decision-making in urban planning, infrastructure development, and disaster mitigation strategies in the future.